Predefined-Time and Prescribed-Performance Control Methods Combined with Second-Order Terminal Sliding Mode Control for an Unmanned Planing Hull System with Input Delay and Unknown Disturbance - Seongik Han (Journal of Marine Science and Engineering, 2023)
In this study, we investigate a terminal sliding mode control (TSMC) system combined with predefined-time and prescribed-performance control methods for an unmanned planing hull (UPH) system in the presence of a control input delay at the heading axis and a porpoising motion due to pitching-moment disturbance. A second-order TSMC system is adopted to bypass the unstable heading-angle response of the conventional first-order TSMC system caused by the control input delay of the hydraulic rudder actuator system. Next, predefined-time and prescribed-performance control methods are proposed to enhance the disturbance rejection performance of an uncertain UPH. The results of sequential comparative simulations show that the disturbance rejection performance of the proposed hybrid disturbance rejector using both the predefined-time and prescribed-performance control methods for a porpoising motion is superior to those of conventional controller systems without introducing disturbance observers.